Mesh simplification - Ghosh, Deboshmita (2024)
An initial mesh is received comprising a hand of a subject. The initial mesh includes a plurality of vertices. A smoothed mesh is generated, and a discrete curvature of the smoothed mesh is determined for each vertex. One or more candidate finger vertices are identified based upon a determination that the discrete curvature for each of the one or more candidate vertices is greater than or equal to a threshold curvature. One or more seed vertices are identified from among the one or more candidate finger vertices based upon a determination that the discrete curvature for one or more other vertices within a neighborhood of each seed vertex is greater than or equal to the threshold curvature. Dilation is performed on the one or more seed vertices to grow one or more patches from the one or more seed vertices. The one or more patches are deprioritized for mesh simplification.